TEKNIK SOSIODRAMA DALAM BIMBINGAN KELOMPOK UNTUK MENGEMBANGKAN KOMUNIKASI INTERPERSONAL SISWA SMA - Syalafiah, Marinda; Rima, Irmayanti (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2020)
The background of this study is the problem in high school students, namely the inability of students to interpersonal communication. Students who have difficulty doing interpersonal communication will find it difficult to adjust to the surrounding environment. So that the behavior exhibited by students such as tend to withdraw and take aggressive actions, difficult to adjust, easy to get angry, tend to force the will, selfish, and want to win themselves so that they are easily involved in disputes. Efforts are made to overcome these problems by using group guidance services through sodiodrama techniques. The purpose of this study is to examine the effectiveness of group counseling to develop interpersonal communication of high school students. The method used in this research is a literature review method that can help in providing context and meaning in the writing that is being done. and the researcher can state explicitly from the results of the study and the reader knows why the thing to be investigated is a problem that must be examined, both in terms of any subject in terms of the relationship of research with other relevant research.keywords:Â Interpersonal Communication, Group Guidance, Sociodrama Techniques.